If f (x) = x² + 3 and g (x) = 3x - 1 then find the following:

1a. (f+g)(x)

1b. (f+g)(3)

1c. (f-g)(x)

1d. (fg)(x)

1e. (fg)(-1)

1 answer

1a. (f+g)(x) = f(x)+g(x) = x^2 + 3 + 3x - 1 = x^2 + 3x + 2

1b. (f+g)(3) = 9+3+2 = 14

1c. (f-g) = x^2 - 3x + 4

1d. (fg)(x) = f(x)*g(x) = (x^2+3)(3x-1) = 3x^3 - x^2 + 9x - 3

1e. (fg)(-1) = -3 - 1 - 9 - 3 = -16
Similar Questions
  1. Given the function: f(x) = x^2 + 1 / x^2 - 9a)find y and x intercepts b) find the first derivative c) find any critical values
    1. answers icon 1 answer
  2. Given the function: f(x) = x^2 + 1 / x^2 - 9a)find y and x intercepts b) find the first derivative c) find any critical values
    1. answers icon 0 answers
  3. Let equation of an hyperbola be y^2-4x^2+4y+24x-41=0a. Find the standard form b. Find the center c. Find the vertices d. Find
    1. answers icon 0 answers
  4. For the following graph:a. Find the domain of f. b. Find the range of f. c. Find the x-intercepts. d. Find the y-intercept. e.
    1. answers icon 1 answer
more similar questions